Comparison of laboratory and imaging methods associated with bone metabolism in patients with or without renal failure under the age of 45 years with elevated parathyroid hormone levels - Peynirci, Hande; Ersoy, Canan; Gürsoy, Vildan; Girgin, Ayten; Aşık, Mehmet Ali; Gültepe, Ahmet; Özkaya, Güven; Isıktas Sayılar, Emel; Ersoy, Alpaslan (The European Research Journal, 2019)
Objectives: Although bone biopsy is considered the gold standard for the definitive diagnosis of renal osteodystrophy; it is not suitable for routine clinical practice due to its invasive nature. The present study was aimed to evaluate and compare the bone mineral status using dual energy X-ray absorptiometry of patients with or without chronic kidney disease in young population with elevated parathyroid hormone levels. Methods: This was a single center, cross-sectional, retrospective study conducted in patients younger than 45 years of age. The study was performed in the outpatient clinic of a university hospital. Patients with elevated parathyroid hormone levels were included. Results: Among them, 29 had renal insufficiency, 158 had normal renal function. Measured bone mineral density with dual energy X-ray absorptiometry and laboratory values were collected from patient files. The primary end point was to assess the efficiacy of dual energy X-ray absorptiometry in patients with or without renal failure. Except Z score at Ward’s triangle, all of the T and Z scores at lomber, femur neck, trochanteric, and intertrochanteric areas were found significantly lower in patients with chronic kidney disease compared to those without (p < 0.001). Conclusion: Dual energy X-ray absorptiometry seemed to be a reliable method for detection of osteoporosis in premenopausal female and male patients younger than 45 years of age with or without renal failure with elevated parathyroid hormone levels.